2009
DOI: 10.1111/j.1537-2995.2009.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of platelet components prepared with photochemical pathogen inactivation treatment during a Chikungunya virus epidemic in Ile de La Réunion

Abstract: INTERCEPT-CPAs were well tolerated in a broad range of patients, including infants. ATR incidence was low and when present ATRs were of mild severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 19 publications
2
101
0
6
Order By: Relevance
“…68 This theory was put into practice during the La Réunion outbreak when, in 2006, French authorities implemented mandatory photochemical treatment of platelet components with the INTERCEPT Blood System to reduce the risk of CHIKV transmission on La Réunion. 32 Approximately 4,000 platelet units were administered over the course of 1 year, and no transfusion related CHIKV transmissions were documented. Although pathogen inactivation obviously adds cost to blood components, in the context of the current testing paradigm and assuming that there is no established nucleic acid test assay for a specific pathogen, it has been found that pathogen inactivation is more cost effective than NAT in terms of quality-adjusted life years, a measurement of clinical and cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…68 This theory was put into practice during the La Réunion outbreak when, in 2006, French authorities implemented mandatory photochemical treatment of platelet components with the INTERCEPT Blood System to reduce the risk of CHIKV transmission on La Réunion. 32 Approximately 4,000 platelet units were administered over the course of 1 year, and no transfusion related CHIKV transmissions were documented. Although pathogen inactivation obviously adds cost to blood components, in the context of the current testing paradigm and assuming that there is no established nucleic acid test assay for a specific pathogen, it has been found that pathogen inactivation is more cost effective than NAT in terms of quality-adjusted life years, a measurement of clinical and cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 5-day shelf life of platelet components precluded their being delivered to La Réunion from France and pathogen inactivation was instituted on an emergency basis to provide safe platelets for patients there. 32 The relatively short duration of the viremic period (6-7 days) and low rates of asymptomatic infections (3% to 25%) [34][35][36] have been proposed as factors that decrease the risk of contamination of donated blood with CHIKV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done with photochemical treatment by Amotosalem and UVA, a technology that is efficient against the vast majority of known pathogens and which might also prevent the transmission of unknown pathogens (25,(38)(39)(40)(41) INTERCEPT technology is routinely used for PI of PLTs and plasma for clinical use as it is able to inactivate a wide spectrum of bacteria, viruses, and parasites, as well as contaminating leukocytes (42)(43)(44)(45)(46). INTERCEPT process and nucleic acids targeting PI technology is not, however, effective against prion diseases, therefore the risk of prion transmission by treated lysates would remain.…”
Section: Discussionmentioning
confidence: 99%
“…Present examples for pathogens transmissible by blood transfusions requiring additional safety measures are the West Nile virus (WNV), severe acute respiratory syndrome (SARS) virus, Dengue virus, Chikungunya virus, and the parasites Trypanosoma cruzi (Chagas disease), Plasmodium falciparum (malaria) and Babesia spp. (babesiosis) [9,10,11]. Table 1 gives an overview of the haemovigilance data of 3 European countries derived from the literature.…”
Section: Introductionmentioning
confidence: 99%